(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Aim. Design of a program for the use of ethnic games and means to improve the physical development and physical fitness of residents of the middle mountains of 50-55 years of age in gender division.Methods. The survey involved 45 people. In the group of ethnic games - 16 people (8 men and 8 women), in the group of modern physical culture (MFE) - 29 people (17 men and 12 women). Standard methods were used to determine anthropometric indicators. A set of tests for the study of physical qualities was used to assess general fitness levels. According to Student's t-test, mathematical and statistical methods were applied.Results. Comparative analysis of the results showed that the data of the 2nd survey are ahead of the results of the initial measurement in terms of chest circumference, body weight in men (reliability - P <0,05). In women in the group of modern physical education, the indicators are higher than in the 2nd survey, which indicates the effectiveness of the physical activity used. In terms of speed, speed-power qualities, and endurance, there is a significant increase in results (P <0,05); (P <0,01); (P <0,001) and positive dynamics in the 2nd survey in the gender division. Between the results of the 2nd survey and the group of modern physical culture in men, the endurance indicator is significantly higher (P <0,05). The indicators of speed-strength qualities and endurance of women have a significant difference (P<0,05), (P <0,001). The indications in males at the second examination and in the group of modern physical culture in both groups are rated as "high" based on the results of maximum oxygen consumption. The level of physical fitness according to K. Cooper is assessed as “high” and “excellent”.Conclusion. The use of ethnic games and modern means of physical culture contributes to the improvement of physical activity in the age group of 50-55 years.